(untitled) (Research, Society and Development, 2021)
The present study aimed to evaluate the applicability and accuracy of the Body adiposity index (BAI), as an alternative for assessment the body composition of female athletes of high competitive level of martial arts (karate), through the distance imposed in the current period. of the pandemic by COVID 19 and rationalization in obtaining anthropometric measurements. Fifteen ranked athletes from the São Paulo Olympic Karate Project (KSPO) of the São Paulo Karate Federation (FPK) were evaluated. The data collected were: body mass, height, skinfolds and hip perimeter, to obtain the percentage of fat (%BF) and calculation of the body mass index (BMI) and central adiposity (BAI). For statistical analysis and obtaining the correlation coefficient, the R program (2020) was used. There was a strong positive correlation (r=093) between IAC and %BF. This study is the first to find an alternative for the assessment of the body composition of female martial arts athletes (karate), for use in monitoring the assessment of body composition during the pandemic by COVID -19. Still as a perspective, it would be important to apply this and other indexes in other combat sports modalities, both in female and male athletes.